El tejido de la brisa : nuevos asedios a la obra de Marvel Moreno y Germán Espinosa - Ortega González-Rubio, Mercedes; Araújo Fontalvo, Orlando; Illán Bacca, Ramón, 1938- (Área metropolitana de Barranquilla (Colombia) : Universidad del Norte Editorial, 2017)
This book examines the narrative works of writers Marvel Moreno and Germán Espinosa: their themes, forms and resources, in order to determine their inscription in the canon of Colombian and Latin American literature.
Includes bibliographical references.
Online resource; title from PDF title page (Digitalia, viewed January 10, 2019)
Keywords: Moreno, Marvel -- Criticism and interpretation; Espinosa, Germán, -- 1938-2007 -- Criticism and interpretation; Colombian fiction -- History and criticism; Electronic books